The Under appreciated Role of Lifestyle and Nutrition in Cancer Prevention, Genesis, and Treatment (Journal of Cancer Research Updates, 2018)
This article presents a review of the impact of nutrition and lifestyle on the most frequently occurring cancers, including blood, bone, brain, breast, gastric, lung, oral, pancreatic and skin cancers. Heart disease and cancer are the leading causes of morbidity and mortality and the first and second leading causes of death in the United States. Risk of death declined more steeply for heart disease than cancer, offsetting the increase in heart disease deaths, which partially offsets the increase in cancer deaths resulting from demographic changes over the past four decades. Lung cancer is by far the most common cause of cancer-related mortality worldwide in many countries. The incidence rates of lung, colorectal and prostate cancers will continue to rise in the future decades due to the rise of ageing population. Pancreatic cancer is an aggressive malignancy with a poor long-term survival and there has been only slight improvement in outcomes over the past 30 years. Some of the most common contributing factors to various cancers include: genetics, tobacco use, infections, obesity, poor diet, physical inactivity, environmental pollution and hazards, ionizing and ultra-violet radiation (UVR), sunlight, cancer causing substances, chronic inflammation and immunosuppression. This article summarizes recent and tangible cancer control measures which include early detection, weight control, Mediterranean type diet, phytochemicals such as flavonoids, regular physical activity, therapeutic agents, chemotherapy, nano-medicine, medicinal plants and education through mass media awareness.